Analisis Kesulitan Mahasiswa Tentang Pembelajaran Pecahan Pada Soal Fara’id - Netriwati, Netriwati (Analisis: Jurnal Studi Keislaman, 2016)
The phenomenon that occurs among students is their difficulty in detailing and classifying the divisions of inheritance. After examining the material is indeed difficult to understand, particularly on the details of each one received by the heirs is very closely related to the learning of mathematics in the sub material fractions. Lacks of time allocation in this material, resulting in them not getting examples of variety problems.The method used is descriptive qualitative method. This method seeks to describe and interpret what is in accordance with the conditions emerging in the ongoing process. Based on the phenomena that occur in the field can be concluded that the difficulties experienced by students is at determines the parts that must be accepted by the heirs who have been set in the Quran is difficult to be applied in everyday life, Islam has set out clearly in al-Quran but this has not been implemented properly. Another difficulty was experienced on learning math equation that is in the denominator of the fraction obtained by heirs who are entitled to receive too many legacies.